The Relationship of Brith Ball Therapy on Primigravida Mothers With A Fair Delivery Process - Novianti Novianti; Feva Tridiyawati (STIKep PPNI Jawa Barat, 2022)
Aims: Pain in childbirth has the highest degree of pain, caused many women are not ready to have children because day imagine the pain that wiil be presented at the time of labor later. Objectives: The general objective of this study was to determine whether there was an effect of brith ball therapy on pain intensity in labour. Methods: Pain was measured using numeric pain scale from 0 to 10 (0 indicating no pain and 10 indicating severe pain). Univariate and bivariate analysis using Wilcoxon test analysis. Results: Of the 50 respondent mothers who carried out the variable therapy pre-test british ball who were very painful and 29 respondents had pain (58%) and a minority had little pain, 21 people (42%). And on the post-test respondent the least pain was increased by 32 respondents (64%), While the minority of pain was quite severe as many as 18 respondents (36%). A 0.00<0.05. The result are expected to have an effect on british therapy on labor pain. The results of the Wilcoxon test analysis with a dgree of significance(a)=0.05 and a P value of 0.00 were obtained (a<0.05) which can be seen from the value which means that Ho is rejected and Ha is accepted. Conclusion: there is an effect british ball therapy on labor pain. Future studies should be conducted using bigger sample size to explore the true effect using experimental study.